A nationwide analysis of 30‐day adverse events, unplanned readmission, and length of hospital stay after peripheral nerve surgery in extremities and the brachial plexus. Issue 2 (15th April 2018) - Martin, Enrico; Muskens, Ivo S.; Senders, Joeky T.; Cote, David J.; Smith, Timothy R.; Broekman, Marike L. D.
Abstract : Background: Little is known on adverse events and their timing after peripheral nerve surgery in extremities. The aim of this study is to identify predictors and typical timing of complications, unplanned readmission, and length of hospital stay for patients undergoing peripheral nerve surgery in the extremities. Methods: Data were extracted from the National Surgical Quality Improvement Program (NSQIP) registry from 2005 to 2015. Adult patients undergoing peripheral nerve surgery in the extremities were included. A subgroup analysis was performed for brachial plexus operations. Multivariable logistic regression was performed to identify predictors of any complication, surgical site infection, unplanned readmission, and reoperation. Results: A total of 2, 840 patients were identified; 628 were brachial plexus operations. Overall complications were 4.4% and 7.0%, respectively. Median time for occurrence of any complication was 8 days. The most common complications were wound‐related (1.7%), which occurred at a median of 15 days postoperatively. Reoperation occurred in 1.8% of all cases; most commonly for musculoskeletal repair (16.7%). Unplanned readmissions occurred in 2.3% and were most often due to wound‐related problems (24.1%). Preoperatively contaminated wounds, inpatient procedures, and longer operative time seemed to have the most influence on all adverse events. In brachial plexus pathology, insulin‐dependent diabetes and emergency cases also negatively affected outcomes. Conclusions: Complications usually occur one to two weeks postoperatively. Preoperatively contaminated wounds, inpatient procedures, and longer operative times influence outcome. Anatomical level of operation results in significantly different lengths of hospital stay; brachial plexus pathology has the longest length of stay.